How should I solve this?

The parallel sides AB, PQ, and CD, gives similar triangles, ∆ABD ~ ∆PQD and ∆CDB ~ ∆PQB, from which we have;
[tex] \frac{1}{x} + \frac{1}{y}= \frac{1}{z}[/tex]
From the given information, we have;
According to the ratio of corresponding sides of similar triangles, we have;
[tex] \frac{x}{z} = \mathbf{\frac{BD}{QD} }[/tex]
[tex] \frac{y}{z} = \frac{BD}{ BQ} [/tex]
Which gives;
[tex] \mathbf{\frac{y}{z}} = \frac{BD }{ BD - Q D} [/tex]
[tex] \frac{z}{y} = \frac{BD - QD }{ BD } = 1 - \frac{Q D }{ BD}[/tex]
QD × x = BD × z
BD × z = (1 - QD/BD) × y = y - (QD × y/BD)
Therefore;
BD × z = y - (QD × y/BD)
BQ × y = y - (QD × y/BD)
BQ × y = y - (z × y/x) = y × (1 - z/x)
(1 - z/x) = BQ
BD × z = y × (1 - z/x)
BD = (y × (1 - z/x))/z
Therefore;
QD × x = y × (1 - z/x)
(BD-BQ) × x = y × (1 - z/x)
(BD-(1 - z/x)) × x = y × (1 - z/x)
BD = (y × (1 - z/x))/x + (1 - z/x)
BQ + QD = (1 - z/x) + (y × (1 - z/x))/x
BD = BQ + QD
(y × (1 - z/x))/x + (1 - z/x) = (y × (1 - z/x))/z
(1 - z/x)×(y/x + 1) =(1 - z/x) × y/z
Dividing both sides by (1 - z/x) gives;
y/x + 1 = y/z
Dividing all through by y gives;
(y/x + 1)/y = (y/z)/y
Therefore;
[tex] \frac{1}{x} + \frac{1}{y}= \frac{1}{z}[/tex]
Learn more about characteristics similar triangles here:
https://brainly.com/question/1799826
#SPJ1